Capital Income Taxation in the Netherlands - Klemm, Alexander (IMF Working Papers; Working Paper, 2021)
This paper looks at capital income taxation in the Netherlands from an international and domestic perpective. The Netherlands is a major conduit country for FDI. Recent reforms taken by the Dutch authorities as well as public statements represent a strong move to address international tax avoidance, but it is too early to be able to detect the impact in the data, and measuring tax avoidance even in the past is fraught with difficulties. Domestically, the unique system, which for many financial assets effectively taxes wealth rather than capital income, leads to inequities and distortions. Owner-occupied housing is strongly tax-favored and in many cases effectively subsidized. Various reforms, not necessarily of a fundamental nature, would improve efficiency and equity.